Purple corn extract improves benign prostatic hyperplasia by inhibiting 5 alpha-reductase type 2 and inflammation in testosterone propionate-induced rats - Kim, Sung-Ok; Choi, Arin; Lee, Hee-Hwan; Lee, Jae-Yong; Park, Sang Jae; Kim, Byung-Hak (Frontiers in Pharmacology, 2025)
Benign prostatic hyperplasia (BPH) is a health issue caused by an enlarged prostate in older men. Its prevalence increases with age, and it results in urination-related problems. This works studied the effect of purple corn extract (PCE) on improving BPH symptoms using a testosterone propionate (TP)-induced rat model. PCE reduced the enlargement and weight of the prostate through the inhibition of the conversion of testosterone to dihydrotestosterone (DHT) by inhibiting 5α-reductase type 2 (Srd5a2) in TP-induced BPH rats. In these rats, PCE decreased androgen receptor (AR) expression, AR-mediated signaling, and cell proliferation and increased apoptotic cell death. Finally, PCE exhibited anti-inflammatory activity through the regulation of the nuclear factor-kappa B (NF-κB) and nuclear factor erythroid 2-related factor 2 (Nrf-2) axis. These results indicate that the Srd5a2 inhibition and anti-inflammatory activity are some of the beneficial effects of PCE that improve BPH symptoms.